Opioid Use and the Risk of Falls, Fall Injuries and Fractures among Older Adults: A Systematic Review and Meta-Analysis. (4th February 2020) - Yoshikawa, Aya; Ramirez, Gilbert; Smith, Matthew Lee; Foster, Margaret; Nabil, Anas K; Jani, Sagar N; Ory, Marcia G
Abstract: Background: There is increasing concern about opioid use as a pain treatment option among older adults. Existing literature implies an association between opioid use and fracture, increasing the risk of death and disabilities; yet, this relationship with other fall-related outcomes has not been fully explored. We performed a meta-analysis to evaluate the associations between opioid use and adverse health outcomes of falls, fall injuries, and fractures among older adults. Methods: A systematic literature search was conducted using nine databases: Medline, Embase, CINAHL, PsycInfo, Global Health, Northern Light Sciences Conference Abstracts, Cochrane CENTRAL, WHO International Clinical Trials Registry Platform, and ClinicalTrials.gov. We log-transformed effect sizes (relative risk [RR], odds ratio [OR], and hazard ratio [HR]) to compute pooled risk estimates comparable across the studies. The random-effects model was applied to calculate the pooled risk estimates due to heterogeneity. Meta-regressions explored differences in risk estimates by analysis method, study design, setting, and study quality. Results: Thirty studies, providing 34 relevant effect sizes, met the inclusion criteria for this meta-analysis. Overall, opioid use was significantly associated with falls, fall injuries, and fractures, with effect sizes ranging from 0.15 to 0.71. In meta-regressions, no selected factors explained heterogeneity. Conclusion: While heterogeneity is present, results suggest an increased risk of falls, fall injuries, and fractures among older adults who used opioids. Findings highlight the need for opioid education and nonopioid-related pain management interventions among older adults to decrease fall-related risk.